Langya henipavirus: Is it a potential cause for public health concern? - Shania Sanchez; Hinh Ly (Virulence, 2023)
ABSTRACT A new virus, named Langya henipavirus (LayV), has recently been identified in Shandong and Henan provinces in China and has so far infected 35 individuals between April 2018 and August 2021. It is closely related to other known henipaviruses (Nipah and Hendra viruses) that can cause up to 70% human case fatality. Even though LayV has not been shown to be fatal in humans and does not appear to be transmitted from human-to-human, it is an RNA virus with the capacity to evolve genetically in the infected hosts (e.g. shrews) and can infect humans (e.g. farmers who have been in close contacts with shrews). It is therefore important to be vigilant about this new viral outbreak.